Establishment of Systematic Strategic Planning Procedure for China’s Green Coal Logistics by using Interpretative Structure Model - Kao, Ching-Kuei (Archives of Business Research, 2020)
In today’s society with a globalized economy, countries around the world are pursuing efficiency while also pursuing environmentally sustainable development. Therefore, studying green coal logistics for environmental development and optimization is of great significance and practical value. On the basis of the green concept framework of coal logistics, this paper will determine the five main problems in the operation of green coal logistics and then propose seven improvement strategies to these five main problems by using TRIZ theory. Interpretative structural modeling (ISM) is used to establish a systematic development procedure of green coal logistics strategy to examine the development of green coal logistics. The analysis results of ISM indicate that, when developing green coal logistics, coal enterprises should retain the effective operation of the original operating mechanism. At the same time, enterprises should introduce a green coal logistics system and effectively merge the two to establish a simple and effective logistics system operating mechanism and cultivate employees’ awareness of environmental protection. Doing so will establish a green image of coal enterprises and decrease the cost of green logistics of coal enterprises. Next, each department within the coal enterprise should be refined. To enable various departments within the coal enterprise to improve work efficiency through information sharing and exchange, the operation process of each department needs to be standardized and the source and the scope of information of each department must be clarified. Finally, through the production, storage, sharing, and transfer of knowledge of information, coal enterprise employees can be assisted to effectively carry out green awareness popularization courses so they can acquire, produce, store, share, and transfer the knowledge of green coal logistics to enable coal enterprises and employees to understand the relationship between the development of green coal logistics and environmental protection.